Electrical characteristics of gallium–indium–zinc oxide thin-film transistor non-volatile memory with Sm2O3 and SmTiO3 charge trapping layers. Issue 12 (11th February 2015) - Her, Jim-Long; Chen, Fa-Hsyang; Chen, Ching-Hung; Pan, Tung-Ming
<x xml:space="preserve">Abstract</x> In this study, we report the structural and electrical characteristics of high-κ Sm2O3 and SmTiO3 charge trapping layers on an indium–gallium–zinc oxide (IGZO) thin-film transistor (TFT) for non-volatile memory device applications.